The limnological conditions of a tropical nursery pond used for production of helostoma temmincki fry - Cheah, Sin Hock; Abd. Satar, Mustafa Kamal; Md. Yusoff, Fatimah (Malaysian Society of Applied Biology, 1988)
A Iimnological study was conducted in a tropical nursery pond used for fry production of Helostoma temmincki. Water temperature, light, dissolved oxygen, conductivity, total alkalinity, pH, nitrates, phosphates, phytoplankton density and biomass, zooplankton density, benthos and fish were sampled and analyzed weekly during the 4 week study period. Oxygen concentrations were low (2.42-4.28 mg/l), The water was acidic (pH: 5.78-6.64) with low alkalinity (14.89-28.40 mg CaC03/l)· Inorganic nitrogen values were relatively low (0.051-0.092 rng N/1) in relation to orthophosphate concentration (0.030-0.064 mg/l) for balanced phytoplankton uptake. Phytoplankton density and biomass were low with ranges of 413-3046 cells/ml and 12.05-27.88 mg Chlorophyll a mg/m3 respectively. Zooplankton density was also low (44.8-460 organisms/l). The water was clear with light penetration reaching pond bottom. Chironomus formed 77% of the total benthos which comprised of 8 species. Two mollusc species Gyraulus convexciusculus and Melanoides tuberculata formed the next abundant group. H. temmincki fry had an average growth of 1.5 mm/day and 46.4 mg/day and a survival rate of 16.4%. Improvements in nursery pond management to enhance fry production are discussed